Adaptation of love addiction inventory to Turkish culture: a validity and reliability study - Traş, Zeliha; Yakıcı, Hikmet Beyza (Journal of Dependence, 2024)
Objective: This study aimed to translate, adapt, and assess the validity and reliability of the "Love Addiction Inventory" and "Love Addiction Self-assessment" developed by Costa et al. into Turkish for measuring love addiction.. Method: Data for the Love Addiction Scale and the Love Addiction Scale Short Form were collected from two separate study groups. For the Love Addiction Scale, measurements were gathered from 694 individuals aged between 18 and 50 (mean age = 25.50). For the Love Addiction Scale Short Form, data were collected from 485 individuals aged between 18 and 50 (mean age = 26.04). The research utilized the Love Addiction Scale, Young Internet Addiction Test Short Form, Bergen Social Media Addiction Scale, and Love Addiction Scale Short Form as data collection instruments. Results: The Turkish adaptation of the Love Addiction Scale, initially comprising six factors, revealed six distinct subfactors. Internal consistency coefficients for these sub-factors ranged from .90 to .97, indicating strong reliability. Similarly, the Love Addiction Scale-Short Form retained its single subscale structure from the original version, with an internal consistency coefficient of .87. Co-validity assessments with the Young Internet Addiction Test Short Form and the Bergen Social Media Addiction Scale yielded significant findings, affirming the validity of the scales. Conclusion: This study’s findings affirm that both the Love Addiction Scale and its Short Form are valid and reliable instruments for assessing love addiction within Turkish culture. These scales play a crucial role in exploring the underlying factors contributing to love addiction specifically in the Turkish context.